2017
DOI: 10.35188/unu-wider/2017/353-0
|View full text |Cite
|
Sign up to set email alerts
|

Polygamy and female labour supply in Senegal

Abstract: In this paper, we explore the links between polygyny and female labour supply in Senegal using a nationally representative survey. In a reduced-form approach, we first measure the impact of polygyny on participation using a joint model of spouse participation. The identification of the impact of polygyny relies on the use of district-level variables as instruments. We find a positive impact of polygyny on female labour force participation. Turning to a structural approach based on the collective household mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Agadjanian and Ezeh (2000) found that women in high-polygyny areas are less likely to work outside the home compared to those in low-polygyny areas of Ghana. In contrast, Cudeville et al (2017) found that polygamy increases the hours a woman works because of sharing tasks among the women in the household. In Senegal, hours worked by women in polygamous households in urban areas are higher than those in rural areas.…”
Section: Literature Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…Agadjanian and Ezeh (2000) found that women in high-polygyny areas are less likely to work outside the home compared to those in low-polygyny areas of Ghana. In contrast, Cudeville et al (2017) found that polygamy increases the hours a woman works because of sharing tasks among the women in the household. In Senegal, hours worked by women in polygamous households in urban areas are higher than those in rural areas.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Social norms and traditional social arrangements can also pose barriers to the labour market for women. In this line, we want to look at the role of polygamy (especially polygyny, where a man has multiple wives) as a determinant of FLFP because, so far, the evidence on the effect of polygamy is mixed (Agadjanian and Ezeh 2000;Cudeville et al 2017). In West Africa, polygyny is still widespread, reported to be practised by 30-50 per cent of households (Cudeville et al 2017;SWAC/OECD 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another custom that can undermine women's bargaining power includes polygyny (Lawson et al, 2015), with the threat that the husband will take a second wife (Cudeville et al, 2017).…”
Section: Contextmentioning
confidence: 99%